Stephen Chaudoin, Helen V. Milner, Xun Pang, “International Systems and Domestic Politics: Linking Complex Theories with Empirical Models in International Relations” (International Organization, 2015)
Following older debates in international relations literature concerning the relative importance of domestic versus systemic factors, newer debates emphasize interdependence among states and the complex interactions between systemic and domestic factors. As globalization and democratization advance, theories and empirical models of international politics have become more complicated. We present a systematic theoretical categorization of relationships between domestic and systemic variables. We use this categorization so that scholars can match their theory to the appropriate empirical model and assess the degree to which systemic factors affect their arguments. We also present two advances at the frontier of these empirical models. In one, we combine hierarchical models of moderating relationships with spatial models of interdependence among units within a system. In the other, we provide a model for analyzing spatial interdependence that varies over time. This enables us to examine how the level of interdependence among units has evolved. We illustrate our categorization and new models by revisiting the recent international political economy (IPE) debate over the relationship between trade policy and regime type in developing countries.